(untitled) (World Bulletin of Management and Law, 2025)
The article discusses and analyzes the importance and priorities of the "green" economy in the context of the implementation of the concept of sustainable development, the effectiveness of the model of its future development, the main stages of a comprehensive assessment of "green" growth and effective environmental policy.